There's something happening here : the New Left, the Klan, and FBI counterintelligence - Cunningham, David, 1970- (University of California Press, 2004)
Cunningham explores the FBI's COINTELPROs against white hate groups and the New Left to examine how agents dealt with the hundreds of individuals and organizations labelled as subversive threats. The author focuses on the complex organizational dynamics which generated the thousands of COINTELPRO actions.